Le Cyrano de Bergerac de Jacques Prévot - Madeleine Alcover (Les Dossiers du GRIHL)
In his last book on Cyrano’s life and works, Jacques Prévot mainly repeats his 1977-1978 doctoral thesis. As far as biography is concerned, important components, particularly two related to religion and to the army, are ignored or underevaluated. The discovery of Cyrano’s maternal genealogy has revealed, in 2000, a milieu of very pious people, some of which were influent in the Compagnie du Saint-Sacrement, and, more recently, the discovery of the conversion of Cyrano’s paternal grand-father to Protestantism brought a new light on a possible tension in the family and on the writer’s repeated comments on Catholic Church’s dogmas. About Cyrano’s military carrier Prévot’s informations are generally totally outdated (Lacroix, 1858 and Lachèvre, 1921), although we learned in 2009 that the writer entertained a relationship with his former captain in the Gardes du Roi, Alexandre de Biran de Casteljaloux (“Carbon de Casteljaloux” in Rostand’s play) ; the officer lived in Clamart, not far from the castle of Mauvières, property of the Cyrano family, and, in Paris, he was in the Marais where Cyrano moved in 1649. Castelgeloux had a strong attachment to Jean de Cuigy, the landlord of Clamart and the “notaire secrétaire du roi” who signed the authorisation (“privilège”) to print posthumously Cyrano’s novel, Les Etats et Empires de la Lune, and Cuigy had a long relationship with Tanneguy Regnault des Boisclairs, the last protector of the writer, all installed rue de la Verrerie or in its close neighborhood. As we see, many events of Cyrano’s biography appear now as linked together through this group of old and influential friends. As far as the history of Cyrano’s works is concerned, Prévot, who seems not to have a clue of what material bibliography means and to have a very poor knowledge about censorship at this time, could not analyse the social and financial effects of the previous censorship of the Lettres (1654) on the “cleaning” of Cyrano’s novel before its publication in1657. I have proved in 2009, thanks to a variant the content of which refers to an event posterior to Cyrano’s death, that Le Bret indeed was involved in this rewriting in 1657. Furthermore, the corpus variorum provided by Prévot in 1998, although very faulty, has confirmed (without Prévot knowing it ?) my theory that the posthumous version descended from two different manuscript branches used one after the other, which makes dubious that Le Bret received the novel from Cyrano with the mission to publish it. At the end of the article are examined two attributions, one about a substitution concerning the most important philosophical “treatise” in the novel and the other about the attributions, after Lachèvre, of seven mazarinades to Cyrano, although a stylistic test, inspired by Harold Love’s works, has established in 2004 the total improbability of these attributions to Cyrano ; but Prévot does not refute his adversaries, he just continues to assertdogmaticallyhis opinions…